PRZEKONANIA STUDENTÓW FILOLOGII ANGIELSKIEJ NA TEMAT NAUCZANIA GRAMATYKI - Pawlak, Mirosław; Mystkowska-Wiertelak, Anna; Bielak, Jakub (Neofilolog, 2019)
Learners’ beliefs concerning the process of learning and teaching a foreign language without doubt play a very important role since they can determine the effectiveness of the instructional techniques and procedures that are employed by teachers, thereby considerably influencing the outcomes of that process. This applies in equal measure to teaching all the language skills and subsystems, including grammar instruction, or, more generally, form-focused instruction. In view of such considerations, the aim of the present paper is to report the findings of a study which sought to tap the beliefs of 106 Polish students of English philology with respect to such issues as the choice of the syllabus, the degree of integration of focus on form with meaning and message conveyance, the ways in which grammar structures are introduced and practiced as well as the provision of corrective feedback on grammar errors. The data were collected by means of a questionnaire specifically designed for this purpose (Pawlak, 2012, 2013b), which contained both Likert-scale and openended questions related to all of these areas. The analysis of the data demonstrates that the participants manifest clear preferences with respect to the process of learning and teaching grammar, which, on the one hand, may provide a basis for introducing modifications into grammar classes taught to English majors, and, on the other, makes it possible to identify areas that should be given more emphasis in the course of educating future teachers of English.